An optimal protection scheme for spatially distributed UHVDC transmission systems - HU Yunpeng; TANG Jun; ZHANG Jianfeng; ZHANG Yiyong; ZHANG Jing; WANG Junsheng (Zhejiang dianli)
Spatially distributed UHVDC transmission systems eliminate the need for AC transmission lines converging at a converter station by enabling DC power transmission at remote locations. However， this change in topology introduces new challenges for DC protection. To address protection failure in the operating station after faults occur in the bipolar neutral bus area and grounding electrode line area of low-end nonoperational station， improved protection criteria are proposed based on theoretical analysis and simulation tests. Additionally， the shortcomings of existing fault isolation measures for grounding faults on the low-voltage side of the DC filter at the high-end terminal are analyzed， and a fault isolation scheme for the DC filter is proposed. Finally， the characteristics of differential protection in the DC field are examined， and optimal protection criteria are introduced and validated using real-time digital simulation （RTDS） system.